Method to produce controlled release formulation of 1-Naphthaleneacete, a plant growth regulator. - Hussein, Mohd Zobir; Zainal, Zulkarnain; Yahya, Asmah; Wong, Dickens Vui Foo (2007)

(untitled)
A process of producing nanocomposite wherein an inorganic layered hydroxide (LDH) is used as a matrix hosting a plant growth regulator consisting of 1-napthaleneacetate (NAA) wherein the process consists of preparing aqueous solution by dissolving Zn(NO3)2 and Al(NO3)3 at molar ratio satisfying the condition of 2.